Peat Water Treatment Using Chitosan-Bentonite, Surfactant Modified Bentonite And Natural Zeolite - Zakaria, Siti Nor Farhana (2014)
The peat swamp is one of the largest wet land coverage in Malaysia. Its ability to retain water even during drought makes the peat swamp a valuable resource to a variety of flora and fauna. In light of the recent water shortage issue, peat water was included in the list as one of the potential alternative water resources. However, due to its acidic nature, high organic matter and heavy metal (iron) contents, peat water is unsuitable to be supplied directly to consumers. Therefore, methods to remediate peat water from pollutant were defined in this study. After a six month monitoring at the Beriah swamp, Perak, it was found that peat water contains a high concentration of heavy metal iron, is turbid, brownish and acidic. In this study, two methods were used i.e. the jar test and the column study. The materials used in the jar test were chitosan, natural bentonite, modified bentonite, its combination and composite. In the column study, additional adsorbents such as natural zeolite and activated carbon were used to enhance the purification of the samples. The experiment was designed and analysed using Response Surface Methodology (RSM) in order to determine their interactions with the samples. Based on the efficiency in remediating peat water samples, the combination of chitosan-natural bentonite in the jar test was chosen as the best material. This combination had recorded removal 78% colour, 89% turbidity, 90% iron and 67% Chemical Oxygen Demand (COD) in natural peat water pH 4.80. The flocs formation which was observed in the Scanning Electron Microscopy (SEM) image and the size increment resulting from the Mastersizer analysis had proven that this combination had an affinity towards the pollutant elements.